Two dogs in a trench coat go to school - Falatko, Julie (Falatko, Julie. Two dogs in a trench coat., 2018)
"Sassy and Waldo are good dogs. Sassy and Waldo spend their day keeping the house safe. Has a squirrel ever gotten inside? No! But every day their boy, Stewart, leaves for a scary place: School! Sassy and Waldo need to save Stewart. But they don't let dogs into school. Not even the really good ones. Sassy and Waldo put on a trench coat. Now everyone at Bea Arthur Elementary thinks they are a new student. Everyone except Stewart"--Page 4 of cover.